2011
DOI: 10.3892/ijo.2011.1173
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RHOXF2 (PEPP2) as a cancer-promoting gene by expression cloning

Abstract: Abstract.Multiple mutations contribute to establish cancers. We have searched for potential oncogenes by screening cDNA libraries derived from gastric cancer cell lines, pancreatic cancer cell lines and glioma cell lines, using retrovirus-mediated expression cloning. Two types of interleukin-3 (IL-3)-dependent cell lines, Ba/F3 and HF6, were transduced with the cDNA libraries and several genes that render these cells factor-independent were identified including PIM-1, PIM-2, PIM-3, GADD45B and reproductive hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, PEPP2 expression in PBMNC or BMMNC from healthy donors was not observed or was extremely low compared to leukemia cells, which suggests that PEPP2 is an ideal target for therapy of leukemia. We didn’t observe high expression of the PEPP2 gene in other types of cancer cells including brain tumor, lung cancer, and pancreatic cancer, although it has been reported that this gene is expressed in colon cancer and gastric cancer [ 26 ], which were not included in our sample set.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, PEPP2 expression in PBMNC or BMMNC from healthy donors was not observed or was extremely low compared to leukemia cells, which suggests that PEPP2 is an ideal target for therapy of leukemia. We didn’t observe high expression of the PEPP2 gene in other types of cancer cells including brain tumor, lung cancer, and pancreatic cancer, although it has been reported that this gene is expressed in colon cancer and gastric cancer [ 26 ], which were not included in our sample set.…”
Section: Discussionmentioning
confidence: 88%
“…Li et al [ 25 ] showed that knockdown of Rhox5 in a colon cancer cell line suppressed cell proliferation and migration in mice. There is also a report that transducion of PEPP2 into murine monocytic leukemia cell line enhanced leukemogenesis in irradiated mice [ 26 ]. These results indicate an important role of PEPP2 in the development of leukemia and suggest that targeting PEPP2 might be effective in the eradication of leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, RHOXF2 has been confirmed to be higher expressed in various cancer cell lines, such as lung cancer, colon cancer and leukemia cell lines. 26 In breast cancer patients, it was considered as a recognized biomarker at the transcript level. 27 Compared with normal tissue, the expression of RHOXF2 in breast cancer was upregulated by 3.31 fold in breast cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…ODF is involved in sperm tail maintenance and centrosome matrix [269] which facilitates the tumor cell proliferation. The RHOXF2 is associated with cell transformation [270] and cell to cell contacts [271]. The ODF4 and RHOXF2 cancer testis antigens had overexpression in tumors compared with normal marines in a sub population of Iranian BC patients [272].…”
Section: Main Textmentioning
confidence: 99%